2022
DOI: 10.3390/geriatrics7020027
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation Therapy with Nebulized Capsaicin in a Patient with Oropharyngeal Dysphagia Post Stroke: A Clinical Case Report

Abstract: Dysphagia and aspiration risk are common sequelae of stroke, leading to increased risk of stroke-associated pneumonia. This is often aggravated by stroke-related impairment of cough, the most immediate mechanical defense mechanism against aspiration. In humans, reflex cough can be repeatedly and safely elicited by inhalation of nebulized capsaicin, a compound contained in chili peppers. Could this cough-eliciting property of capsaicin support the recovery of stroke survivors who present with dysphagia and aspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…A possible hypothesis is that capsaicin should aid the clearance of the laryngopharynx and lower airways. In addition, a repeated trigger of the cough reflex might induce a central recovery of the cough reflex contributing to dysphagia rehabilitation as demonstrated in a recent case report in subjects affected by stroke [29] and in tracheostomized subjects affected by hemorrhagic stroke [30]. Another study conducted by Cui et al demonstrated an improvement in the swallowing function by combining ice and capsaicin stimulation in subjects with dysphagia after stroke [31].…”
Section: Discussionmentioning
confidence: 96%
“…A possible hypothesis is that capsaicin should aid the clearance of the laryngopharynx and lower airways. In addition, a repeated trigger of the cough reflex might induce a central recovery of the cough reflex contributing to dysphagia rehabilitation as demonstrated in a recent case report in subjects affected by stroke [29] and in tracheostomized subjects affected by hemorrhagic stroke [30]. Another study conducted by Cui et al demonstrated an improvement in the swallowing function by combining ice and capsaicin stimulation in subjects with dysphagia after stroke [31].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, we defined the incidence of aspiration and the length of hospital stay as the secondary outcomes. In this meta-analysis, we included dysphagia-caused aspiration, a common stroke sequela caused by bulbar palsy, as it increases the risk of SAP ( 29 ).…”
Section: Methodsmentioning
confidence: 99%